PENGARUH BEBAN KERJA, KONFLIK DAN KOMPENSASI TERHADAP TURNOVER INTENTION KARYAWAN (EVISCERASI) RUMAH PEMOTONGAN AYAM CV. WAHANA BERKAH SEJAHTERA DI BOYOLALI - Fiqri Syahrul Mubarak; Sutarno Sutarno (CV. KAMPUS AKADEMIK PUBLISING, 2026)
CV. Wahana Berkah Sejahtera is a company operating in the poultry slaughterhouse industry, particularly in the evisceration section, which involves high physical work demands. These conditions potentially create workload and work conflict that may influence employees’ intention to leave the company (turnover intention). This study aims to analyze the effect of workload, work conflict, and compensation on employee turnover intention at CV. Wahana Berkah Sejahtera. This research is a survey study using a quantitative non-experimental design. The data source used in this study is primary data. The sample consists of 100 respondents, representing all employees of CV. Wahana Berkah Sejahtera, with total sampling applied as the sampling technique. Data were collected through questionnaires and literature study. The validity test results for workload, work conflict, compensation, and turnover intention variabels show a significance value of 0.000 < 0.05, indicating that all variabels are valid and reliable. The results of this study indicate that workload and work conflict have a significant effect on employee turnover intention, while compensation has no significant effect on employee turnover intention at CV. Wahana Berkah Sejahtera. Based on these findings, the researcher recommends that the company manage workload more proportionally and improve communication and work conflict resolution mechanisms, while future researchers are encouraged to include additional variabels to enhance and refine further studies.